The Effect of CSR and Ownership Structure on Environmental Innovation: The Moderating of CEO Narcissism - Erna Wati; Sari Dewi; Iskandar Itan; Finia Novarisy Zultia (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
In the context of increasing global awareness of environmental sustainability and the growing pressure on corporations to adopt responsible business practices. This study examines the effects of CSR performance and ownership structure, specifically insider ownership and institutional ownership, on environmental innovation, while also considering the moderating effect of CEO narcissism in Indonesian listed companies. Using purposive sampling, this study focuses on firms listed on the Indonesia Stock Exchange between 2019 and 2022 that published sustainability reports. The results show that CSR performance has a significant positive effect on environmental innovation, indicating that higher CSR engagement leads to greater environmental innovation, while insider ownership and institutional ownership have no significant direct effects on environmental innovation. In terms of moderation, CEO narcissism does not significantly moderate the relationship between CSR and environmental innovation, but it significantly moderates the relationship between ownership structure (insider and institutional ownership) and environmental innovation. Environmental innovation is primarily driven by CSR performance, whereas the influence of ownership structure depends on CEO narcissism as a key moderating factor. This study contributes to the literature by integrating CSR, ownership structure, and CEO behavioral traits in explaining environmental innovation in an emerging market context.